Peranan program acara stasiun TVRI NTB sebagai salah satu media edukasi kesehatan pendengaran - Eka Arie Yuliyani; Didit Yudhanto; Wahyu Sulistiya Affarah; Eva Triani; Faisal Libryan; Dewa Agung Istri Sintha Prajnyaswari (Universitas Mataram, 2022)
Television is one of the modern mass media that has the potential to convey information to the public and can also shape and build a person's character and behavior. Not only national media, but local media also play an important role in health education activities. In commemoration of World Hearing Day, Unram Hospital cooperates with local station TVRI NTB to hold a health program through the “Sehat Bugar” program providing education about ear and hearing health as a promotive and preventive effort. The purpose of holding this activity is to raise high awareness among individuals, especially the young millennial generation, regarding their daily attitudes in order to maintain healthy ears and hearing. The activities of the millennial generation who like to listen to music with earphones at a loud volume and for a long period of time can be at risk of hearing loss. The presence of hearing loss is often not realized because they are used to ignoring ear health. Hearing loss can cause barriers to communication and have an impact on a person's quality of life. Therefore, cleanliness and ear health are important things that must always be considered and maintained. As an evaluation, this health education activity can be accepted by the community. In practice, the live streaming of this television program has been watched 624 times. In addition, this can also be used as an evaluation to carry out health education activities better in the future.